Peran Kepuasan Pelanggan sebagai Mediasi Pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan: Studi Kasus pada Kaluma Casual Dining & Bar - I Kadek Pasek Juniarta; Ni Putu Nina Eka Lestari (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
In today’s intensely competitive casual dining market, “good” service alone is insufficient to secure loyalty; loyalty is forged through genuinely satisfying experiences. This study examines customer satisfaction as a mediator linking service quality to customer loyalty at Kaluma Casual Dining & Bar, Sanur. A quantitative design was employed with 120 respondents (purposive sampling, ages 17–55). Data were gathered via a 5-point Likert questionnaire and analyzed using PLS-SEM (SmartPLS 4.1.1.4). Results indicate: (1) service quality → customer satisfaction is positive and significant (β=0.623; p<0.001); (2) customer satisfaction → loyalty is significant (β=0.615; p<0.001); (3) the direct path service quality → loyalty is positive but not significant (β=0.149; p=0.052); and (4) customer satisfaction significantly mediates the effect of service quality on loyalty (indirect effect β=0.383; p<0.001). Theoretically, the findings reinforce SERVQUAL and the Disconfirmation Paradigm by showing that loyalty emerges via satisfaction rather than from perceived quality alone. Managerially, firms should prioritize consistent delivery across reliability, responsiveness, assurance, empathy, and tangibles to maximize satisfaction—the psychological bridge—to sustained revisit intention, positive word-of-mouth, and customer commitment.